A shift to libertarian paternalism in old‐age income security: Discourses on pension privatization reforms in Lithuania 2016–2018. (13th June 2021) - Juska, Arunas
Abstract: This study uses news media discourse analysis to investigate the highly contentious process of pension privatization retrenchment in Lithuania. In 2016, Lithuania began debating reforms on restructuring its poorly performing "second pillar" pension scheme – statutory funded individually defined contribution plans managed by the private sector. Pension reform is here conceptualized as a process of discursive contestation of the orthodox neoliberal consensus that prevailed in designing and introducing a private pension system in the early 2000s. By 2018, when a new Law on Pensions institutionalized a subsidized "nudge‐type" private retirement saving scheme, this process was legitimized by a newly prominent libertarian paternalistic ideology. Impacts of the discursive framing of pension reforms on their outcomes are discussed. Abstract : Cette étude recourt à l'analyse des discours médiatiques pour examiner le processus extrêmement controversé d'assouplissement de la privatisation des régimes de retraite en Lituanie. En 2016, la Lituanie a commencé à discuter de réformes visant à restructurer son régime de pensions du «second pilier», qui enregistrait des résultats médiocres – ce régime est basé sur des plans statutaires individuels à cotisations définies gérés par le secteur privé. La réforme des pensions est ici conceptualisée comme un processus de contestation discursive du consensus orthodoxe néolibéral qui prévalait lors de la conception et de l'introduction d'un système de pensions privé au début des années 2000. En 2018, lorsqu'une nouvelle loi sur les pensions a institutionnalisé, comme une sorte de «coup de pouce», un régime privé d'épargne‐retraite subventionné, ce processus a été légitimé par une idéologie paternaliste libertaire devenue récemment dominante. Les répercussions de la caractérisation discursive des réformes des retraites sur leurs résultats sont abordées. Abstract : En este estudio se utiliza el análisis del discurso de los medios de información para investigar el muy controvertido proceso de privatización de las pensiones en Lituania. En 2016, Lituania comenzó a estudiar la posibilidad de realizar reformas para reestructurar su poco eficiente régimen de pensiones de "segundo pilar", a saber, los regímenes obligatorios individuales de cotización definida financiados por capitalización y de gestión privada. La reforma de las pensiones se conceptualiza en este artículo como un proceso de contestación discursiva frente al consenso neoliberal ortodoxo que prevaleció al diseñar e introducir un sistema de pensiones privado a principios del decenio de 2000. Para 2018, cuando la nueva ley de pensiones institucionalizó un régimen privado de ahorro para la jubilación, subvencionado y que actuaba como catalizador, este proceso ya estaba legitimado por una emergente y notoria ideología paternalista libertaria. En el presente artículo se abordan las repercusiones que la estrategia discursiva sobre las reformas de las pensiones tuvo en los resultados. Abstract : Diese Studie untersucht den stark umstrittenen Prozess des Rückbaus der Rentenprivatisierung in Litauen durch eine Analyse des Diskurses in den Nachrichtenmedien. 2016 begann man in Litauen, über Reformen zur Restrukturierung des wenig erfolgreichen Rentensystems der zweiten Säule zu diskutieren. Bei diesem System handelte es sich um obligatorische privatwirtschaftliche Rentenpläne mit Kapitaldeckung und individuell festgelegten Beiträgen. Die Rentenreform bestand darin, dass die streng neoliberale Sichtweise hinterfragt wurde, die bei Entwurf und Einführung des privaten Rentensystems Anfang der 2000er‐Jahre bestimmend gewesen war. 2018, als mit dem neuen Rentengesetz ein bezuschusstes privates Rentensparprogramm nach dem Prinzip der motivierenden Steuerung ( nudging ) in Kraft trat, wurde dies mit der neu aufkommenden Theorie des libertären Paternalismus legitimiert. Diskutiert wird in der Studie, inwieweit sich das diskursive „Framing"von Rentenreformen auf deren Ergebnisse ausgewirkt hat. Abstract : В данном исследовании анализируется полемика в средствах массовой информации о весьма противоречивом процессе ограничения приватизации системы пенсионного обеспечения в Литве. В 2016 году в стране началось обсуждение реформ, направленных на реструктуризацию недостаточно эффективной пенсионной системы «второй опоры» – программ, финансируемых из государственного бюджета, но управляемых частным сектором с индивидуально установленными размерами взносов. Обсуждение пенсионной реформы в СМИ представлено как полемика на тему традиционного неолиберального консенсуса, преобладавшего во время разработки и внедрения частной схемы пенсионного обеспечения в начале 2000‐х годов. К 2018 году, когда новый закон о пенсиях институционализировал субсидируемую частную пенсионную накопительную программу «подталкивающего типа», этот процесс был легитимизирован недавно завоевавшей популярность идеологией либертарианского патернализма. Влияние дискурса на формирование представления о пенсионных реформах и на их эффективность всё ещё обсуждается. Abstract : 本研究采用新媒体话语分析, 对立陶宛饱受争议的养老金私有化过程进行了调查。2016年, 立陶宛开始讨论重组改革表现不佳的"第二支柱"养老金制度, 该计划由私营部门管理, 法定筹资方式为个人确定缴费。养老金改革引发了对传统新自由主义共识的散漫式争论, 21世纪早期在设计和引入私人养老金制度时, 传统新自由主义曾盛行一时。2018年, 新《养老金法》将有补贴的"助推式"私人退休储蓄计划制度化, 新出现的自由家长制意识形态使这一过程合法化。本文讨论了养老金改革论述框架对其改革成果的影响。 Abstract : تستخدم هذه الدراسة تحليلاً لمناقشات وسائل الاعلام الإخبارية من أجل البحث في عملية الخفض من خصخصة المعاشات التقاعدية التي تثير جدلاً واسعاً في لتوانيا. ففي عام 2016، بدأت لتوانيا في مناقشة إصلاحات من أجل إعادة هيكلة خطة معاشاتها التقاعدية القائمة على "الدعامة الثانية" ذات الأداء الضعيف، وهي خطط ممولة قانوناً وقائمة على الاشتراكات المحددة بشكل فردي يديرها القطاع الخاص. ويجري تصوير إصلاحات المعاشات التقاعدية على أنها عملية طعن استطرادي في توافق الآراء الليبرالية الجديدة التقليدية السائدة في تصميم نظام معاشات تقاعدي خاص واستحداثه في بداية مطلع القرن الحالي. وبحلول عام 2018، عندما أضفى قانون جديد بشأن المعاشات التقاعدية طابعاً مؤسساتياً على خطة مدخرات التقاعد الخاصة المبسطة والمدعومة مالياً، اكتسبت هذه العملية شرعية من خلال إيديولوجية أبوية تحررية برزت مؤخراً. وتُناقش آثار الصياغة الخطابية لإصلاحات المعاشات التقاعدية على النتائج الخاصة بها. Abstract : Este estudo usa a análise do discurso da mídia para investigar o processo altamente controverso de reversão da privatização da previdência na Lituânia. Em 2016, a Lituânia começou a debater reformas sobre a reestruturação do seu regime de pensões de "segundo pilar" de fraco desempenho – planos estatutários de contribuição definida, financiados individualmente e administrados pelo setor privado. A reforma da previdência neste caso é conceituada como um processo de contestação discursiva do consenso neoliberal ortodoxo que prevaleceu na concepção e introdução de um sistema de previdência privada no início dos anos 2000. Em 2018, quando uma nova legislação previdenciária institucionalizou um regime de poupança subsidiado para aposentadoria privada do tipo "nudge", esse processo foi legitimado por uma ideologia paternalista libertária que se tornara proeminente. Os impactos da captura discursiva das reformas previdenciárias em seus resultados também foram analisados.